International perspectives on public health and palliative care - Sallnow, Libby.; Kumar, Suresh, 1961-; Kellehear, Allan, 1955- (Routledge studies in public health., 2012)
"Public health approaches to palliative care have been growing in policy importance and practice acceptance. This innovative volume explores the major concepts, practice examples, and practice guidelines for this new approach.The goal of continuity of care - seamless support for patients in their experiences and transitions from community to primary health services to inpatient services - means that health promotion and community development become important ways to achieve a holistic health approach to end of life care. In developing contexts, where hospitals and hospices may be inaccessible, a public health approach provides not only continuity of care but greater access to good end of life care. This book provides both a historical and conceptual overview whilst offering practical case examples from affluent and developing contexts, in a range of clinical settings. Finally, it draws together research-based guidelines for future practice. Essential reading for public health researchers and practitioners with an interest in end of life care and global health as well as those involved in developing palliative care provision, International Perspectives on Public Health and Palliative Care is the first volume to present an overview of theory and practice in this emerging field"--Provided by publisher.